Peranan Guru dalam Mewujudkan Pendidikan Karakter Era Kurikulum Merdeka: The Role of Teachers in Realizing Character Education in the Independent Curriculum Era - Yanti, Yuli; Juliansyah, M. Eko; Erlina, Erlina; Hijriah, Umi; Irfani, Bambang (STAI Publisistik Thawalib Jakarta, 2024)
The Merdeka Curriculum emphasizes the role of teachers in shaping students' character. This research was conducted using a qualitative method with a systematic literature review approach, analyzing scientific articles by Indriani et al. (2023), Khairiyah et al. (2023), and Putri et al. (2023), which discuss the role of teachers in character education in the Merdeka Curriculum era. Data validation was carried out through source triangulation to obtain a comprehensive understanding. The findings indicate that the application of Student-Centered Learning (SCL) in the Merdeka Curriculum helps students develop character traits such as independence, creativity, and mental resilience, which are essential for facing future challenges. Project-Based Learning (PBL) enhances critical thinking, creativity, discipline, teamwork, and responsibility. Differentiated learning provides space for students to learn according to their interests, talents, and styles, boosting motivation, engagement, and appreciation for diversity. Additionally, the role of teachers as facilitators is crucial in developing students' character, including independence, leadership, and empathy, which supports their academic, social, emotional, and moral development. Conclusion: Character education in the Merdeka Curriculum era shapes academically intelligent students with strong moral and social values to face future challenges.